Assessment Guidelines for Promoting Moral Intelligence for Lower Secondary Students - Prasertsin, Ujsara; Srihaset, Kamontip (Rajapark Journal, 2023)
The purposes of this research were: 1) to determine criteria for moral intelligence assessment and guidelines for presenting the results of the moral intelligence assessment to lower secondary school students; and 2) to search for guidelines to promote moral intelligence for lower secondary school students. The sample was 14 educational and academic experts and 2,000 lower secondary students from 25 schools across the country, selected by purposive sampling. The tools used for collecting data are focus group conversation note forms and assessing moral intelligence. The data were analyzed using frequency, mean, standard deviation, and content analysis. The research results were found as follows: 1) For moral intelligence, there are three important issues: (1) defining moral intelligence assessment criteria; (2) recording and reporting results; and (3) reviewing the quality of measurement manuals. 2) In searching for guidelines to promote them, it was found that there should be a clear, easy-to-understand report on results that was easy to use for all groups. A T-score assessment should be developed by the program. Organizations should play a common role in integrating policy into action, propelling, supporting, and managing learning through a variety of techniques while taking into account the suitability of the age range.